Preoperative subjective impairments in language and memory in brain tumor patients - Rybka, Lena; Jonkers, Roel; Burzlaff, Milena; Rosenstock, Tizian; Vajkoczy, Peter; Picht, Thomas; Faust, Katharina; Rofes, Adrià (Frontiers in Oncology, 2024)
BackgroundSubjective reports can reveal relevant information regarding the nature of the impairment of brain tumor patients, unveiling potential gaps in current assessment practices. The co-occurrence of language and memory impairments has been previously reported, albeit scarcely. The aim of this study is therefore to understand the co-occurrence of subjective language and memory complaints in the preoperative state of brain tumor patients and its impact on Quality of Life (QoL).Methods31 brain tumor patients (12 LGG, 19 HGG) underwent a semi-structured interview to assess subjective complaints of language deficits, co-occurrences between language and memory dysfunction, and changes in QoL. Group and subgroup analyses were conducted to provide general and tumor grade specific data.Results48.4% of patients mentioned co-occurrence of language and memory impairments in reading, writing, and conversation. The HGG group reported co-occurrences in all three of these (reading: 31.6%; writing: 21.1%; conversation: 26.3%), while the LGG only described co-occurrences in reading (25%) and conversation (8.3%), although these were not statistically significant. All patients with co-occurring language and memory deficits reported these to be linked to reduced QoL (48.4%). In patients with an HGG, this number was slightly higher (52.6%) than in patients with an LGG (41.7%).ConclusionLanguage impairments co-occur with memory dysfunction as perceived in patients’ daily life. Patients see these impairments as affecting their quality of life. Further attention to dedicated language and memory tasks seems necessary.